Experimental investigation on oxidation of sulfurized rust in oil tank. (November 2015) - Dou, Z.; Jiang, J.C.; Zhao, S.P.; Mao, G.B.; Zhang, M.G.; Wang, L.; Wang, Z.R.
Abstract: Oxidation of sulfurized rust in oil tank is complicated, and it is influenced by numerous factors such as water content, air humidity, operating temperature etc. The paper focuses on the oxidation process of sulfurized rust in the wild. Firstly, samples collected from a petrochemical company were put into the sulfurization & oxidation experimental apparatus to gain wet and dry sulfurized rusts. Their chemical compositions and phase were analyzed by Energy Dispersive X-ray Spectrometer (EDS) -scanning electron microscope (SEM) technique. The results showed that both wet and dry sulfurized rusts had S, Fe2 O3, Fe3 S4 and FeS2, whereas FeS only existed in wet sulfurized rust. The two kinds of rusts gave a short length of side, diamond appearance and a large pore size in structure. Then oxidation of wet sulfurized rust was investigated, which included electrochemical reaction stage, electrochemical & chemical reaction coexisting stage and chemical reaction stage. The final oxidation product of wet sulfurized was determined to be Fe2 O3 . On the basis of this study, an indicator for monitoring and early-warning was proposed to prevent plants in vicinity of the accidental vessel or tank from fire and explosion. Highlights: A sulfurization & oxidation experimental apparatus was constructed for the formation & oxidation of sulfurized rust. Both wet and dry sulfurized rusts have S, Fe2 O3, Fe3 S4 and FeS2, as FeS only existed in wet sulfurized rust. The oxidation of wet sulfurized rust with wet air included three stages. Oxidation product of wet sulfurized was determined to be α -Fe2 O3 . An indicator for monitoring and early-warning was proposed.